EXPLORING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE PRODUCTION OF DEEPFAKE CONTENT FOR SOCIAL MEDIA: A TECHNOLOGICAL AND SOCIAL ANALYSIS - Singh, Akanksha; Martolia, Mukta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial intelligence and deepfakes are relatively new, with people still getting used to technology and a growing trend and desire for audio and visual content—such as self-made movies for events or social media profile building—in both cases. When people want to represent content for users of social media or want to make movies with any website or application that is available, they run into problems. The article details how deepfakes are allowing incorrect information to be transmitted through these kinds of films and how quick corrections like face or body swapping and backdrop removal are now available. This research study's goal is to investigate how artificial intelligence can be utilized to produce realistic deepfakes that everyone can produce and distribute online without requiring any technological expertise. People searching the internet for software to create deepfakes is another major issue; nevertheless, they should also look for information regarding the dependability of these movies.